Structural empowerment and mental health in healthcare professionals: The role of civility - Ribeiro, Luísa (2021)
Quality of the work environment is a factor that promotes workers’ mental health and it’s a present concern for the European Agency for Safety and Health at Work. There is a need to understand the factors that can promote better mental health at work and under which circumstances structural empowerment represents a working environment that allows workers’ development, low rates of incivility and positive effects on mental health. The present study aims to verify in which conditions structural empowerment has a positive effect on workers’ mental health, through the mediating role of civility. To that purpose, we have applied the Portuguese versions of WCS, CWEQ-II and the mental health scale from MOS SF-36v2 to a sample of 303 health care professionals in a public-private hospital located in the Greater Lisbon. The results of this study reveal that structural empowerment has a direct positive effect both on workers’ mental health and on workplace civility. However, the indirect effect of structural empowerment on mental health through civility is only effective for health professionals with longer tenure.